Consumer knowledge and awareness of the toxicity and handling of household products at a tertiary care center in Beirut, Lebanon. (July 2022) - Mostafa, Hala; Rizk, Jennifer; Kanaan, Elie; Hamade, Hani; Kaddoura, Rima; Tamim, Hani; Sakr, Carine; El Zahran, Tharwat
Household products intoxication is a common and preventable problem. Household product hazard awareness is lacking among consumers in Lebanon, posing a public health hazard. A cross-sectional observational study was conducted at the American University of Beirut Medical Center by administering surveys to 176 adult participants. The surveys focused on demographics, awareness of product toxicity, practices used to avoid intoxication, and sources of information. Each participant was given a score for behavior and awareness. Informative brochures were handed to increase awareness among consumers. We surveyed 176 patients, of whom (84.7%) were females with a mean age of 42.2 ± 13.5 years. Most were married (77.3%), had a college education (76.7%), were employed (62.5%), and were in charge of household cleaning (76.7%). Toilet cleaners were the substances most perceived to be toxic (94.0%). Most people (86.4%) had low to medium scores on behavior, while most (77.3%) had high scores on awareness. Male gender and using product labels as sources of information were associated with higher behavior scores, while referring to a friend or a relative as a source of information on product intoxication was associated with a lower behavior score. Greater awareness scores were strongly associated with being married, having a higher monthly income, and referring to warning signs presented on the labels as a source of knowledge. Unsafe handling and storage of household products are common among consumers in our population. Therefore, it may be necessary to launch education campaigns to improve consumer handling of household products.